SAVING AND POPULARIZATION OF CREATIVE INHERITANCE OF VASILIY BARVINSCY BY ARTISTS OF UKRAINIAN FOREIGN - Karas, G. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article presents special features of preservation and popularization of Vasil Barvinsky’s creative legacy by the Ukrainians in the context of vocal, choral and instrumental performance as well as Ukrainian musicology of the West Diaspora. Special attention focuses on the publications and recordings of musical works of V. Barvinsky.